A multimodal analysis of social practices in the pandemic period - Molè, Maria Alessandra (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The Covid-19 has affected not only the health of populations but also social practices and their local organization transforming human interactions. Using a multimodal conversation analysis, in this paper we will show how prevention is incarnated in social actions of participants and how Covid-19 affect social interaction.